Behavioral analysis of soil-straw movement in saline-alkali land during rotary tillage using discrete element method - Zhao, Zhuang; Hou, Jialin; Wang, Dongwei; Shang, Shuqi; Guo, Peng; Xia, Chao (International Journal of Agricultural and Biological Engineering, 2025)
Considering the problems of a low soil fragmentation rate and low straw mulching rate in the traditional rotary tiller tillage mode in the saline-alkali land, the layered stubble and soil crushing rotary tillage knife was designed, and the key structural parameters were determined by the analysis of rotary tillage knife-soil-straw movement. The soil-straw movement behavior in saline-alkali land under different working parameters of rotary tillage was analyzed, and the discrete element modeling of soil-straw-rotary tillage in saline-alkali land was established. In addition, the dynamic process of soil-straw aggregate fragmentation in saline-alkali land from a microscopic perspective was systematically explored. Combined with experimental optimization analysis, the optimum working parameters of the saline-alkali rotary tiller were obtained with a forward speed of 2.02 km/h, a working depth of 178.83 mm, and a rotation speed of 324.48 r/min. To verify the field performance of the machine, the soil fragmentation rate, straw burial rate, and tillage depth stability were chosen as test indices for the field trial. The average soil fragmentation rate was 91.85%, the average straw returning rate was 91.09%, and the average stability of tillage depth was 91.12%, indicating that the designed rotary tiller can effectively improve soil crushing and straw burial in saline-alkali land and meet the basic requirements of high-performance seedbed preparation in saline-alkali land. Keywords: saline-alkali land, straw return, soil fragmentation, layered stubble and soil crushing. DOI: 10.25165/j.ijabe.20251804.9349Citation: Zhao Z, Hou J L, Wang D W, Shang S Q, Guo P, Xia C. Behavioral analysis of soil-straw movement in saline-alkali land during rotary tillage using discrete element method. Int J Agric & Biol Eng, 2025; 18(4): 38–52.